(untitled) (Journal of Engineering, 2022)
There are serious environmental problems in all countries of the world, due to the waste material such as crushed clay bricks (CCB) and in huge quantities resulting from the demolition of buildings. In order to reduce the effects of this problem as well as to preserve natural resources, it is possible to work on recycling (CCB) and to use it in the manufacture of environmentally friendly loaded building units by replacing percentages in coarse aggregate by volume. It can be used as a powder and replacing of percentages in cement by weight and study the effect on the physical and mechanical properties of the concrete and the masonry unit. Evaluation of its performance through workability, dry density, compressive strength, thermal conductivity, and absorption test, and the experimental results obtained confirmed the possibility of using the recycling of clay bricks waste as aggregates instead of natural aggregates and reducing the weight, as well as recycling clay bricks waste and using it as a powder. It contains suitable pozzolanic that can be used as a supplementary cement material that reduces the cement content in concrete used to produce load-bearing units.